2007
DOI: 10.1111/j.1462-2920.2007.01425.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of benzene by a marine sulfate‐reducing enrichment culture, and cell hybridization of the dominant phylotype

Abstract: The anaerobic biodegradation of benzene, a common constituent of petroleum and one of the least reactive aromatic hydrocarbons, is insufficiently understood with respect to the involved microorganisms and their metabolism. To study these aspects, sulfate-reducing bacteria were enriched with benzene as sole organic substrate using marine sediment as inoculum. Repeated subcultivation yielded a sediment-free enrichment culture constituted of mostly oval-shaped cells and showing benzene-dependent sulfate reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
76
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 60 publications
5
76
1
Order By: Relevance
“…Our findings that a member of the family Desulfobacteraceae plays a key role in benzene degradation is also supported by a recent study (16) in which a dominant phylotype (clone BznS295) in a benzene-degrading marine sulfate-reducing enrichment culture was closely related to SB-21 and SB-30 (Fig. 3).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Our findings that a member of the family Desulfobacteraceae plays a key role in benzene degradation is also supported by a recent study (16) in which a dominant phylotype (clone BznS295) in a benzene-degrading marine sulfate-reducing enrichment culture was closely related to SB-21 and SB-30 (Fig. 3).…”
supporting
confidence: 75%
“…Bacteria similar to SB-21 have been identified as one of the dominant microbes in benzene-degrading enrichments established from widely dispersed environments such as a Mediterranean lagoon in France (16) and an oil refinery in Oklahoma (30). Furthermore, the abundance of these 16S rRNA gene sequences could also be linked to benzene degradation (16,7). Thus, SB-21 potentially could serve as a biomarker for in situ biodegradation of benzene in the environment under sulfidogenic and methanogenic conditions.…”
mentioning
confidence: 99%
“…Analysis of gene expression patterns indicated that benzene was first metabolized to benzoate (17), which was then metabolized via well-known pathways for anaerobic benzoate metabolism (18). The proposed carboxylation of benzene by F. placidus is consistent with evidence suggesting carboxylation in enrichment cultures (19)(20)(21)(22)(23). A gene encoding a putative benzene carboxylase in F. placidus was identified (17), but further analysis has been limited by a lack of a system for genetic manipulation of F. placidus.…”
mentioning
confidence: 54%
“…So far, only four anaerobic benzene-degrading bacteria have been described, two Dechloromonas strains (strains RCB and JJ) that degrade benzene in conjunction with (per)chlorate (only strain RCB), nitrate, or oxygen reduction (9) and two denitrifying Azoarcus strains (strains DN11 and AN9) (23). The optimal physiological conditions for anaerobic benzene-degrading bacteria and the biodegradation pathways are still largely unclear (6,8,17,26,33,48).…”
mentioning
confidence: 99%